Recycled Waste Materials Proceedings of EGRWSE 2018 - Agnihotri, Arvind Kumar; Reddy, Krishna R.; Bansal, Ajay.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains selected papers presented during the International Conference on Environmental Geotechnology, Recycled Waste Material and Sustainable Engineering (EGRWSE-2018). The papers focus on finding innovative ways of recycling and reusing waste materials, reducing demand for natural resources and processing industrial and chemical wastes such that disposal reduces their environmental burden. This volume will be of interest to researchers, policy makers and practitioners working in the field of waste management. .
Evaluation of Compressibility and Drainage Characteristics of Highly Plastic clay stabilized with Fly ash and Stone quarry dust -- Strength Characteristics of Clayey Soil Stabilized with Nano - Silica -- Chemical Analysis Procedures for Determining the Dispersion Behaviour of Red Mud -- Study and Analysis of Characteristics of Construction and Demolition Waste in Highway Pavements -- Effect of Cement Kiln Dust and RBI Grade 81 on Engineering Properties of Plastic Clay -- Stabilization of silty soil with marble dust and sugarcane bagasse ash -- Strength Improvement of Silt Loam using Egg Shell Powder and Quarry Dust -- Enhancement of Shearing Strength of Poorly Graded Sand by Using Surface Modified Waste Rubber Tyre Fibres -- Effects of granulated ground blast furnaceslag and fly ash on stabilization of soil -- Soil Stabilization Using Plastic Waste -- Effect of fly ash on permeability of soil -- Influence of Waste Marble Powder and Metakaolin on Strength Properties of Concrete: A Short Review -- Review paper on partial replacement of cement and aggregates with various sindustrial waste material and its effect on concrete properties.
Keywords: Engineering geology; Environmental engineering; Biotechnology; Bioremediation; Geotechnical engineering; Geoengineering; Environmental Engineering/Biotechnology.; Geotechnical Engineering and Applied Earth Sciences